India 2024 - Bindloss, Joseph; Bigg, Margot; Choy, Monique; Elliott, Mark, 1963-; Grace, Lucie; Lobo, Christabel; Lobo, Joanna; Noble, Isabella; Noble, John, 1951 October 11-; Raub, Kevin; Sidhu, Puneetinder Kaur; Stafford, Paul; et al. (Lonely Planet guidebooks., 2024)
Discover popular and off the beaten track experiences from marvelling at the carving-covered Sun Temple in Konark, to drifting through the basilicas of Old Goa near Panaji, and grazing the streets after dark at the Sarafa Bazar food market in Indore.